2011
DOI: 10.1063/1.3598322
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical bridge between linear and nonlinear microrheology

Abstract: Stress development, relaxation, and memory in colloidal dispersions: Transient nonlinear microrheology J. Rheol. 57, 457 (2013); 10.1122/1.4775349Rheo-SANS investigation of acicular-precipitated calcium carbonate colloidal suspensions through the shear thickening transitionPassive microrheology exploits the fluctuation-dissipation theorem to relate thermal fluctuations of a colloidal probe to the near-equilibrium linear response behavior of the material through an assumed generalized Stokes Einstein relation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…However, we suspect that our model of Section I A will also differ from the linear coupling model of Démery and Dean in terms of the nonlinear response. In [16], the distortion in φ caused by the object-field interaction vanishes as 1/V p at large velocities, but because of the boundary condition we have chosen, there will always be a non-vanishing distortion in φ, though it may occur in a boundary layer near the protein, as in calculations of the nonlinear microrheological drag in colloidal model systems [53,59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we suspect that our model of Section I A will also differ from the linear coupling model of Démery and Dean in terms of the nonlinear response. In [16], the distortion in φ caused by the object-field interaction vanishes as 1/V p at large velocities, but because of the boundary condition we have chosen, there will always be a non-vanishing distortion in φ, though it may occur in a boundary layer near the protein, as in calculations of the nonlinear microrheological drag in colloidal model systems [53,59].…”
Section: Discussionmentioning
confidence: 99%
“…The integral dℓ (σ + Π) ·n may also be evaluated simply by using an identity derived from the reciprocal theorem [52] of low-Reynolds number fluid mechanics (see [53,54] and references within). This trick lets us determine the total drag force on an object in a fluid flow v in terms of a simpler "reference" flowṽ in the same geometry.…”
Section: Reciprocal Theorem Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for these differences we determined the shear-dependent viscosity TJ( . :Y) of the solution by active microrheology in geometries similar to our microfluidic device [23][24][25][26] . This was achieved by dragging a silica bead ( a = 3p.m) through an unpatterned sample cell of h = 7 p.m height using a scanning optical tweezer.…”
mentioning
confidence: 99%
“…Brady (2010, 2012) demonstrated that fluctuations in the motion of a fixed-force probe can interpreted as a force-induced "microdiffusivity," which encodes information on the normal stress differences in the dispersion. The aforementioned studies have focused on the microstructure between the probe and a bath particle; Squires (2008) and DePuit et al (2011) suggest that it is the (unsteady) nonequilibrium microstructure between pairs of bath particles advected past a moving probe that could be more indicative of the macrorheology of the dispersion, particularly when the probe is much larger than the bath particles. It should also be mentioned that the active microrheology of concentrated dispersions has been addressed via dynamic simulations [Carpen and Brady (2005); Winter et al (2012)] and mode-coupling theories [Gazuz and Fuchs (2013); Voigtmann and Fuchs (2013)].…”
Section: Introductionmentioning
confidence: 99%